Fluoride removal from groundwater using bio-adsorbents - Gebrewold, Berhane Desta; Annachhatre, Ajit P.; Rene, Eldon R.; Lens, Piet N. L.; Thammarat Koottatep; Nguyen, Thi Kim Oanh; Pimluck Kijjanapanich; Netherlands Fellowships Programmes (NFP); UNESCO {u2013} IHE/Asian Institute of Technology (Pathum Thani, Thailand : Asian Institute of Technology, 2016)
In this study, fluoride uptake potential of rice husk carbon and corn cob carbon was investigated through batch and column experiments. Screening analysis was done using thermally activated different bio adsorbents (sugarcane bagasse, corn cob, rice husk, potato peel, papaya seed, groundnut shell and coconut husk). Rice husk and corn cob were selected and further studies were carried on in order to ascertain their adsorption capacities. The selected bio adsorbents were activated thermally and chemically to enhance the surface of the adsorbents for fluoride uptake. Central composite design in Response surface methodology was used in order to generate a combination of different independent variables (pH, initial fluoride concentration, contact time and adsorbent dose) and the results were analyzed using analysis of variance (ANOVA). Fluoride uptake using rice husk carbon showed maximum adsorption efficiency of 91% and capacity of 7.9 mg/gat optimum condition of pH 4, initial fluoride concentration of 18 mg/l, contact time 3 hours and adsorbent dose of 2 g/. whereas fluoride uptake using corn cob carbon resulted maximum adsorption efficiency of 89% and uptake capacity of 5.83 mg/g at optimum condition of pH 6, initial fluoride concentration of 13 mg/l, contact time of 5 hours and adsorbent dose of 2 g/l. Fluoride concentration in treated water was below standard limit in both cases. Equilibrium is attained within 3 hours for rice husk carbon and 5hoursusing corn cob carbon.pHpzc for rice husk carbon and corn cob carbon was obtained to be 6.7 and 2.3, respectively. The adsorption data fitted Langmuir adsorption model describing monolayer adsorption of fluoride on to rice husk carbon and corn cob carbon. Adsorption kinetic model study indicated that fluoride uptake followed pseudo{u2013}second order kinetic model with adsorption rate of 0.384 and 0.366 mg/g.min for rice husk carbon and corn cob carbon, respectively. Intraparticle diffusion was examined in order to determine rate-limiting step and was found that intraparticle diffusion is not a rate-limiting step, rather fluoride adsorption on to rice husk carbon and corn cob carbon was governed by both intraparticle diffusion and surface diffusion / surface adsorption. Column experiments were carried out using three columns packed with 100% rice husk carbon, 100% corn cob carbon and 50% rice husk carbon + 50% corn cob carbon. The breakthrough adsorption capacities were found to be 7.88 mg/g, 5.03 mg/g and 5.22 mg/g, respectively. Breakthrough was attained in 6thday for 100% rice husk carbon and 5th day for the remaining two columns. The results were analyzed using Thomas model, which yields adsorption capacities to be 11 mg/g, 8.1 mg/g and 9.4 mg/g, respectively for the three columns. In general, a satisfactory result was obtained for fluoride uptake using rice husk carbon and corn cob carbon.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Environmental Engineering and Management with specialization in Environmental Technology for Sustainable Development jointly offered by the Asian Institute of Technology, Thailand and UNESCO{u2013}IHE, The Netherlands
AIT-UNESCO-IHE
Thesis (M.Sc.) - Asian Institute of Technology, 2016
Keywords: Water -- Fluoridation; Water -- Softening; Water -- Purification -- Adsorption